2012
DOI: 10.5216/cab.v13i4.19468
|View full text |Cite
|
Sign up to set email alerts
|

Comparação Da Fibra Em Detergente Neutro De Forragens: Desempenho, Digestibilidade E Parâmetros Ruminais

Abstract: Objetivou-se determinar os efeitos da substituição parcial da fibra em detergente neutro (FDN) da silagem de milho pela FDN da cana-de-açúcar in natura ou cana-de-açúcar tratada com NaOH ou feno de alfafa, sobre o desempenho, digestibilidade e parâmetros ruminais de vacas Holandesas em lactação, canuladas no rúmen e no duodeno, distribuídas em um delineamento Quadrado Latino 5×5. Utilizaram-se duas dietas controle, uma com baixo (controle negativo; SMB) e outra com alto (controle positivo; SMA) teor de FDN de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Distinct authors (MARTINS et al, 2006;MACEDO JÚNIOR et al, 2007;SANTOS et al, 2011) reported that the increase of structural carbohydrates occurs parallel to the increase in lignin contents, phenolic component that limits and extension of the fibrous digestion in the rumen, being consistent with those reported in the present research. Lignification restricts the performance of digestive enzymes produced by rumen microorganisms and, hence, decreases digestibility.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Distinct authors (MARTINS et al, 2006;MACEDO JÚNIOR et al, 2007;SANTOS et al, 2011) reported that the increase of structural carbohydrates occurs parallel to the increase in lignin contents, phenolic component that limits and extension of the fibrous digestion in the rumen, being consistent with those reported in the present research. Lignification restricts the performance of digestive enzymes produced by rumen microorganisms and, hence, decreases digestibility.…”
Section: Resultssupporting
confidence: 92%
“…X axis = time in hours; Y axis = Degradation (% of the OM). In the remaining stages, there is a higher concentration of structural carbohydrates and lignin, complicating factors of bulky, mainly because its comprise high variation in their nutritional composition as like as its rate of degradation of its components, varying according to forage species, plant age, time of year, fertilization and management of soil (KASUIYA et al, 2008;LIMA et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The fiber portion represented by the NDF values is formed by cellulose, hemicellulose and lignin, forage digestibility is inversely proportional to these compounds (Mendes et al, 2008;Lima et al, 2012). In this way, most NDFF values found are below those reported by Ribas et al (2007), who assessed two forage maize hybrids and obtained contents over 51% NDF, verifying that the highest values of this fiber portion tend to limit voluntary consumption, resulting in a lower productive performance by animals.…”
Section: Resultsmentioning
confidence: 87%
“…However, by-products of BMB possess fine granulometry and, therefore, result in increased proportions of small particles within the diet as I-BMB increases (Table 4). Other factors, along with rumen filling may affect the regulation of consumption, since passage rates of particles of similar sizes may increase, a circumstance that would reduce the satiety as a result of rumen filling (Lima et al, 2012). However, the thinner the diet, the lower the expected volume of rumen occupation and degree rumen filling, which are factors that have also increased levels of consumption (Mertens, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…This may be a result of reduced levles effective fibre present within diets containing greater percentages of BMB. However, fibrous by-products with small particle sizes are stimulators of rumination, since they form thick rumen supernatant, and thereby stimulate rumination, which can enhance rumination efficiency (Lima et al, 2012). Rum/NDFI ** 2 0,674 0,774 0,908 1,122 0,017 0,647 0,612 Ŷ = 0,648 + 0,019X (R 2 = 88,32%) Rum/ADFI ** 3 0,310 0,468 0,462 0,612 0,004 0,119 0,341 ; 3 Ŷ = 0,329 + 0,012X (R 2 = 93,72%) Chew/DMI ** 4 1,152 2,066 1,954 2,182 0,034 0,156 0,432 Ŷ = 1,649 + 0,025X (R 2 = 90,23%) Chew/NDFI ** 5 0,376 0,432 0,494 0,568 0,002 0,441 0,348 Ŷ = 0,371 + 0,008X (R 2 = 87,23%) Chew/ADFI ** 6 0,174 0,264 0,250 0,308 0,006 0,083 0,546 Ŷ = 0,189 + 0,005X (R 2 = 95,34%) * (% of TT); ** (min g-1 day-1).…”
Section: Data Withinmentioning
confidence: 99%